ANALISIS FAKTOR PENYEBAB KESULITAN BELAJAR MATEMATIKA DI SEKOLAH DASAR - Silvia Tri Anggraeni; Sri Muryaningsih; Asih Ernawati (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Purwokerto, 2020)
Abstract. This research was conducted in grade IV of SD Negeri 2 Penambongan and was aimed at investigating the characteristics of students' learning difficulties, the factors causing difficulties in learning Mathematics, and the efforts conducted to resolve the difficulties of learning Mathematics. This research applied the qualitative approach with a case study design. The participants of the research were principal, class teacher, three grade IV students (chosen by the teacher's recommendation), and parents. The data were collected through observations, interviews, and document collections. The results of the data analysis showed that 1) the characteristics of difficulties in learning Mathematics experienced by the students was the abnormality of visual-spatial perception, 2) the internal factors causing difficulties in learning Mathematics were student's attitude, learning interest, motivation, and ability of sensing, while the external factors causing difficulties in learning Mathematics were learning strategies, learning aid, family, and society, 3) the efforts conducted by teachers to resolve the difficulties in learning Mathematics were motivating and supporting students when finding difficulties, the efforts conducted by students were joining extra courses out of school, and the efforts conducted by parents were motivating and accompanying their children when studying at home.